The Four Causes of ADHD: Aristotle in the Classroom - Pérez-Álvarez, Marino (Frontiers in Psychology, 2017)
ADHD is probably the most controversial psychiatric disorder today. While there is a well-established conception, critics show that it is unsustainable. The controversy does not seem able to go any further than for one side and the other to affirm their positions. Critics must recognize that the “ADHD” they criticize somehow exists. The question would be to see what it is that exists. On the other hand, those who argue for it do not do so without a certain implicit rhetoric and metaphysics. The question here would be how they have come to be as genuinely sure as they are of such a questioned position. The controversy is not resolved in empirical and scientific terms. It requires an ontological and epistemological metascientific reassessment. Aristotle’s Theory of Four Causes – material, formal, efficient and final – is used as an instrument of enquiry. According to this analysis, ADHD is not the pretended clinical entity as presented, but a practical entity providing a variety of functions. The implications would be rather different from the usual.